Thermal state of permafrost in the high mountains of Mexico - Kenji Yoshikawa; Victor Soto; Guillermo Ontiveros-Gonzales; Samael Oliver Vagamontes; Hugo Delgado Granados; Lorenzo Vazquez-Selem; David Palacios (Arctic, Antarctic, and Alpine Research)
This article summarizes the thermal state of Mexican permafrost and its relationship to snow, ice, and geothermal environments. Ice-rich permafrost is observed near the summits of Citlaltépetl (Pico de Orizaba) and Iztaccíhuatl volcanoes. The lower limit of mountain permafrost is about 5,200 to 5,300 m.a.s.l. much higher than originally thought. Some of the sporadic permafrost may still exist on the Little Ice Age rock glaciers, but most of the buried glacial ice between 4,500 and 5,000 m.a.s.l. is slowly decaying and not thermally stable as permafrost. During the summer months, the Inter-Tropical Convergence Zone approaches the Mexican highlands and provides moist conditions sufficient for snow cover at high elevations. Maximum active layer thickness occurred during the snow-free seasons, typically April to July in Citlaltépetl and Iztaccíhuatl, perhaps Popocatépetl, but not Nevado de Toluca, where the summit is below the snowline most of the time today. The diurnal temperature amplitude results in freeze–thaw cycles only near the surface to 15 cm. The importance of the snow cover is that it provides great protection for incoming solar energy penetration, helping to preserve buried glacial ice and permafrost.